طبيعة تصورات أم الطفل الحامل لمتلازمة داون - صحراوي, عقيلة (جامعة الوادي - University of Eloued, 2020)
ملخص تهدف الدراسة الحالية معرفة الوضعية الصعبة المباغتة التي تعيشها أم الطفل المصاب بمتلازمة داون نظرا لشدة وقع صدمة اكتشافها لإعاقة طفلها بما في ذلك من سلوكاتها وطبيعة تصوراتها والديناميكية النفسية التي تعيشها جراء هذه الإعاقة، والتيلا تتوافق مع تصوراتها المنتظرة. في الواقع، إن حجم الإعاقة لدى أم الطفل المصاب يجعلها تعيش آلاما نفسية إلى درجة صعوبة تقبل الإعاقة، مما قد يؤدي إلى هشاشة التنظيم النفسي و فقر التصورات الذهنية المشحونةبالنبذ الصريح أو المقنع ذلك ما سيتم اختباره في إطار المنهج العيادي بالاعتماد على تحليل خطاب الأمهات في المقابلة العيادية إضافة إلى تحليل سياقات اختبار تفهم الموضوع. أسفرت النتائج على أنالمبحوثات تميزن بتوظيف نفسي عصابي( نوع رهابي وآخر وسواسي) نتيجة اضطراب العلاقة الوجدانية بينهن وبين أطفالهن المصابين التي عكستها آلياتهن الدفاعية غير العادية التي برزت من خلال تصوراتهن الذهنية.Abstract: The aim of the present study was to find out the difficult and bewildering situation that a mother of a child with Down syndrome goes through due to the intense shock when she discovers the handicap of her child, including her behavior, the nature of her representations and the psychological dynamics. This child’s disability does not fit with her expected representations. Actually, the magnitude of the handicap makes the mother experience psychological pain to the extent that she refuses her child’s disability. This will lead to a vulnerable psychological organization and poor mental representations expressed by explicit or implicit rejection which we will test by using the clinical method, that is, by analyzing the mothers’ speech during the clinical interview, besides the TAT. The results reveal that mothers have a neurotic psychological functioning (phobic, obsessional), caused by the disturbed emotional relationship with their children, this was reflected by the unusual defense mechanisms revealed by their mental representations.
دراسة حالات
مقال
Keywords: متلازمة داون، ; التصورات الذهنية، ; التوظيف النفسي: Down syndrome, mental representations, psychological functioning